The construction of time, place and society in 21st century American dystopia fiction: a corpus linguistics analysis of deixis - Khalil, Huda H. (Penerbit Universiti Kebangsaan Malaysia, 2020)
With the challenges of the 21st century, there seems to be an urgent need to reflect more on the way literature constructs the world for the sensitive age group of young adults. In this vein, the present paper is an attempt to investigate the way time, place and society are linguistically portrayed for young adults in the interesting literary genre of dystopia science fiction. This attempt is the track that the paper pursues to find out why and how the young adult readers get so indulged with the world of dystopia science fiction. The young adult seems to reconstruct the dystopic science fiction temporal, special and social atmosphere with the aid of language. Thus, there must be a certain linguistic structure for the construction of the three vital elements of the world (time, place and society) in this literary genre. To achieve its aims, the paper combines the concept of deixis with Werth’s (1999) Text World Theory. For more precise results, the corpus linguistics tools of concordance and frequency are employed by using Anthony’s (2019) AntConc software. The data consists of eight young adult dystopia science fiction works; Suzanne Collins’ The Hunger Games Trilogy (2008-2010) (a series of three novels) and James Dashner’s The Maze Runner (2009- 2016) (a series of five novels).